Gender Differences in Students' Continuous Adoption of Mobile Learning in Saudi Higher Education - Albelali, Salma A.; Alaulamie, Abdullah A. (2019 2nd International Conference on Computer Applications & Information Security (ICCAIS), 2019)
With the rapid advance in the internet, mobile information systems have turned into a promised sector within the universal information and communication technology. Saudi ministry of higher education exerts effort to integrate IS and technology into learning especially with the Saudi vision 2030 toward knowledge investment. However, it has been observed that researches overlook the investigation of gender differences in the continuous adoption of M-learning. This study aims to examine the effect of gender on student's perceptions and evaluations of M-learning systems. A total of 640 subjects participated in the experiment. The data analysis illustrates females and males had significant differences among four hypotheses. Males' continuance intention toward using M-learning was stronger than females. Females' attitude towards extrinsic motivations was stronger than males. This study discussed the implications of the results and provided recommendations to enhance students' continuance intention to use M-learning by considering the moderating effect of gender.